REFLEKSI OPORTUNISTIK MANAJEMEN PADA KINERJA PERUSAHAAN SEBELUM DAN SESUDAH RIGHT ISSUE - Andriyani, Lilik (Jurnal Analisis Bisnis Ekonomi, 2008)
Target by this research him is to prove the existence of change of performance which is attitude effected of opportunity time manager of right issue before and after offer of additional equity. Technique intake of sampel use technique of purposive sampling, consist of 16 company of is non financial institution condusting issue right in the year 2003-2005. Data the used is data of sekunder financial statement and year share price3 2001-2007. Monetary ratio to be measured used return in this research cover Current Ratio, Return O nInvesment, Net Profit Margin, Debt To Equity Ratio, Total of Assets Turnover, and share performance measured use return and abnormal of return. Result of test of simultan is there are influence which isnt it attitude of opportunity time and manager of right issue to mentary performance and share performance. Result of test of parsial is attitude of opportunity manager have an effect on to company performance, while time of right issue do not have an effect on to company performance.